ANALISIS KEAKTIFAN SISWA MELALUI PENERAPAN MODEL TEAMS GAMES TOURNAMENT PADA MATA PELAJARAN AKIDAH AKHLAK KELAS XI IPS MAN 2 BUKITTINGGI - Lusiana Halimah; Isnando Tamrin; Syafrizal Syafrizal (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to increase students' activeness in learning by implementing the Teams Games Tournament (TGT) model in the Aqidah Morals subject for class XI IPS at MAN 2 Bukittinggi. This type of research is qualitative research in descriptive form. In conducting this research, researchers go directly to the field (field research) to find out directly about activities related to the problem to be researched. The data collection methods that researchers used in this research were observation, interviews and documentation. Students' activeness in learning can be influenced by the application of models in learning, for this reason various new variations in teaching are needed. Before implementing variations in learning, students were less active and less enthusiastic about learning. After implementing a new variation in learning, namely by implementing the Teams Games Tournament (TGT) model, where students are divided into several small groups then the groups work on the games that are applied and rewards are given to the group that gets the highest score. For this reason, implementing the Teams Games Tournament (TGT) model can increase student activity in learning.